Improving the business environment for micro, small and medium-sized enterprises in Pacific Island countries - Fisher, L.; Francis, Judith Ann; Cruickshank, D.; Dietershagen, Jana (Technical Centre for Agricultural and Rural Cooperation, 2020)
Development of local food crops and fishery value chains for sustaining food systems and enhancing incomes and nutrition in PICs hinges on an enabling environment for the agro-industry – and the private sector as a whole. The potential of agro-based MSMEs to harness innovation, increase economic activity and create employment in support of socio-economic development in the region is undisputed. But, to unleash the potential of these agribusinesses, a conducive and business-friendly environment that promotes entrepreneurship, growth and development is key. The procedures for starting and operating a business in PICs range from following simple to extremely daunting and costly processes, irrespective of size, economic status, and geographic location. The level of complexity depends on the policy, regulatory and legislative environment of the particular country. These factors not only govern how businesses are formed, operate, grow and evolve; they also determine the way business agreements and contractual arrangements are structured and enforced; the way debt recovery, lending and consumer protection are administered; and how property rights are ascertained.